File 59/15 B (A 14) Muscat: slave trade under cover of French flag - Laronce, Lucien-Ernest-Roger; Āl Bū Sa‘īd, Sayyid Fayṣal bin Turkī; Sanani, Abdulla bin Abdurrahman Es; Ali, Saeed bin Saleh bin (British Library, 1902)
The volume comprises correspondence and other papers relating to competing British and French interests in Muscat and Oman at the beginning of the twentieth century. The principal point of contention between British officials, represented by Percy Cox (Muscat Political Agent 1899-1903), was the use of the French flag by Omani vessels, permitted by the French Vice-Consul to Muscat, and regarded by the British as being exploited by the region's slave traders as a means of avoiding interference by British ships. Items of note include a letter from Cox to the Political Resident (Charles Kemball), dated 2 January 1902, discussing relations since 1891 between the Sultan of Muscat and British and French officials, the abuse of the French flag in the town, and the need for diplomatic negotiations between Britain, France and the Sultan to resolve the situation (folios 1F-37). Enclosed with Cox's letter is an eyewitness account (from a British Indian subject residing in Soor [Sur]) of slave trading activity in the town during 1901 (folios 31-35). The file also includes a letter from Cox to his French counterpart (Roger Laronce), dated February 1902, explaining that the Sultan protests at what he describes as the French Government's claims to exercise jurisdiction in Muscat territory over Omani subjects (folios 70-71), and Laronce's reply (folion 73); and a report of a tour of the Muscat coast aboard HMS "Amphritite" by Cox (folios 120-22) and Charles Windham, the "Amphritites's" captain (folios 147-49). Reference is made in a number of pieces of correspondence to a confrontation between Arab slave traders and the Portuguese in Mozambique on 18 March 1902 (folios 117-118, and 140-141). In May 1903 Cox writes to the Political Resident, informing him that he has received information from the British Vice-Consul at Mozambique, of around 100 inhabitants of Muscat and Sur being captured and killed in the confrontation (folios 178-180). Cox uses this incident to repeat his recommendation that a British Agent be installed at Sur (folios 145b-145d). Arrangements are also made to loan the Sultan of Muscat funds to enable him to buy his own steamer (folios 123-127), which Cox hopes will encourage the Sultan to take responsibility for his coast, and in particular Sur (folios 135-138). A blueprint of the steamer acquired for the Sultan is included in the file (foldout plan, folio 169).
Genre: Archival file
Keywords: Esclavage – Oman